Aerobic capacity and lactate production in male Mexican FISU soccer players - Cardenas-Estrada, E.; Tlatoa-Ramirez, H.; Perez-Carcia, J. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: The International University Sport Federation (FISU) is the highest form of participation of athletes of its kind. The institution is also considered one of the highest levels of amateur sport. Aspects included in the preparation for soccer include: technique, tactics, physical preparation, nutrition and psychological. The aim of this study was to determine the maximum aerobic capacity (MAC) and the physical work capacity at 170 beats/min (PWC 170), as well as a workload equivalent to a concentration of lactate of 4.0 mMol/L in Mexican FISU male soccer players Methods A total of 21 male soccer players belonging to the Mexican FISU soccer team, were evaluated on a treadmill to determine their maximum aerobic capacity (MAC) and PWC 170 to a load equivalent to 4.0 mMol/L blood lactate (Lac4.0) Results / Discussion Average and standard deviation: Age: 22.6 +/- 2.2 years; height 175.9 +/- 7.4 cm; weight: 70.2 +/ 7.6 Kg.; MAC: 17.43 +/- 1.80 Km/h; MAC-FC: 180.4 +/- 9.8 bpm; MAC-VO2: 59.7 +/- 2.6 ml/min* Kg. PWC: 14.87 +/- 2.03 Km/h, VO2-170: 50.4 +/- 7.4 ml/min*Kg; Lac 4.0: 14.82 +/- 2.21 Km/h; Lac 4.0- VO2: 50.2 +/- 8.1 ml/min*Kg. The results showed a difference with the published results of soccer players of similar age both as amateurs (Chmari et al, 2005, P <0.01) and as professionals (McMillan et al. 2005. P <0.001). While those selected were eliminated in the semifinals stage during the FISU games, low indices of aerobic capacity can be a determining factor in the performance of those selected to play FISU soccer. Conclusions The low aerobic capacity of the representative FISU Mexican soccer team may be a factor in influencing performance during international competitions.